Optimization of the Synthesis of Nanostructured Tungsten-Molybdenum Bimetallic Oxide. (10th September 2012) - Hassan, H.; Zaki, T.; Mikhail, S.; Kandil, A.; Farag, A.
Abstract : Mo 0.5 W 0 .5 O 3 nanoparticles were prepared through the Pechini process and were characterized using X-ray diffraction (XRD), transmission electron microscopy (TEM), FT-IR spectrometer, and differential thermal analysis (TG-DSC) analyses. The polyesterification reaction, as the starting step, has a profound influence on the dispersion of the resulting nanoparticles. The molar ratios CA : TM = 2 and EG : CA = 1.5 are favorable for the preparation of Mo 0.5 W 0.5 O 3 nanoparticles having average particles size ranging from 2 to 9 nm. Meanwhile, the molar ratios CA : TM = 4 and EG : CA = 0.19 are favorable for the preparation of Mo 0.5 W 0.5 O 3 nanoparticles having an average particles size ranging from 11 to 29 nm. For the calcination step, increased calcination time (eight hours) at 500°C is advantageous for allowing the monometallic phases enough time to transform into the desired bimetallic Mo 0.5 W 0.5 O 3 phase.